Can resistance training change the strength, body composition and self-concept of overweight and obese adolescent males? A randomised controlled trial. Issue 20 (14th August 2013) - Schranz, Natasha; Tomkinson, Grant; Parletta, Natalie; Petkov, John; Olds, Tim
Abstract : Background/aim: Resistance training is an exercise modality at which overweight and obese adolescents can excel and which can therefore positively affect their psychological well-being. The aim of this study was to determine the effect of a 6-month resistance training intervention on the self-concept strength and body composition of overweight and obese adolescent males. Methods: 56 overweight and obese males aged 13–17 years were randomly allocated to an Intervention (n=30) or Control (n=26) group. Primary (psychological) and secondary (strength and body composition) outcomes were assessed at baseline as well as at 3 (halfway through the intervention), 6 (immediately postintervention) and 12 months follow-up. Random effects mixed modelling was used to determine the effects of the intervention. Results: Statistically significant differences between the Intervention and Control groups were observed at 3-month and 6-month assessments for exercise self-efficacy, resistance training confidence and self-esteem. Large increases in strength for the Intervention group, relative to Controls, were also observed with no substantial changes in body composition shown for either group. Values for all variables returned to baseline following completion of the programme. Conclusions: A 6-month resistance training intervention can positively affect the self-concept and strength of overweight and obese adolescent boys.